1999
DOI: 10.1007/s002619900490
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic nodules of the liver: imaging findings

Abstract: Hepatic dysplastic nodules show diverse imaging characteristics with different imaging techniques; however, common imaging findings of hepatic dysplastic nodules are low echo, low attenuation, and high, low, or homogeneous intensity on T1- and T2-weighted MR, and avascularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…2) in 40% and mixed echoic in 10% of detected lesions in our study. Choi et al [21] reported a similar incidence of echogenicity. The hyperechoic feature often reflects steatosis of tumor cells (40% of lesions !2 cm) [22], and the hypoechoic property may be due to the presence of homogeneously compacted cells, i.e.…”
Section: Ultrasonographysupporting
confidence: 50%
“…2) in 40% and mixed echoic in 10% of detected lesions in our study. Choi et al [21] reported a similar incidence of echogenicity. The hyperechoic feature often reflects steatosis of tumor cells (40% of lesions !2 cm) [22], and the hypoechoic property may be due to the presence of homogeneously compacted cells, i.e.…”
Section: Ultrasonographysupporting
confidence: 50%
“…These findings obtained by CTAP and CTHA are very important clinically, and therefore, they should be applied to noninvasive imaging diagnosis such as Doppler ultrasound, dynamic CT and dynamic MRI [28][29][30][31]. In DNs, hypovascularity (less arterial vascularity) relative to the surrounding liver is usually seen.…”
Section: Correlation Between the Blood Supply And Grade Of Malignancymentioning
confidence: 99%
“…However, we wanted to determine the accuracy of imaging techniques as they are performed in routine daily practice in our academic tertiary-care medical center, not in the specific setting of a study in which the radiologist most likely would unintentionally have taken more time and effort to interpret imaging results. Retrospective (re)interpretation of results of imaging examinations by one or more radiologists 19,21,30 includes a similar bias that most likely would lead to greater accuracy than is the case in routine daily practice.…”
Section: Imaging Reports and Radiological-pathological Correlationmentioning
confidence: 99%
“…14,15 Most previous studies have relied on needle biopsies or partial liver resections of focal lesions that were detected by imaging to evaluate the accuracy (sensitivity and specificity) of routine imaging techniques to diagnose HCCs and DNs in cirrhotic liver. [16][17][18][19] However, this type of study cannot correctly determine the accuracy of an imaging technique because patients with (false and true) negative imaging findings are not included, and it sometimes is impossible to distinguish premalignant from malignant lesions on a needle liver biopsy. The true accuracy of an imaging technique can be determined only when imaging data are correlated with the so-called gold standard, which is a detailed pathological examination of complete explant livers with classification of detected focal lesions according to internationally accepted and used criteria.…”
mentioning
confidence: 99%